HUBUNGAN METODE BANDONGAN KITAB TADZHIB TERHADAP MOTIVASI BELAJAR SISWA KELAS XI DI MADRASAH ALIYAH SEBLAK KWARON JOMBANG - Sansiska Ningrum, Lely (Al Tadib : Jurnal Ilmu Pendidikan, 2022)
This research is motivated by how the relationship between the Bandongan Method used in Madrasas and Student Learning Motivation. This study has three problem formulations, namely the bandongan method, learning motivation, the relationship of the bandongan method to the learning motivation of class XI MASS students Seblak Kwaron Jombang. This research is a type of quantitative research with correlational data collection techniques using a questionnaire. The sample in this study amounted to 20 people consisting of several students of class XI MASS Seblak Kwaron Jombang. There are two research variables, namely Bandongan Method (X) and Learning Motivation (Y). The data analysis technique used Validity and Reliability Test Instruments. There are 20 items that are declared valid with a significant level of 0.015. Then to find out whether the instrument is reliable or not, Cronbach's alpha test will be carried out with the acquisition of the Bandongan Cronbach's Alpha Bandongan Test with a value of 0.925> 0.6. While Cronbach's Alpha Learning Reability Learning Motivation is 0.955. From the results of the reliability test of the relationship between Bandongan Method and Learning Motivation, using the Spearman Correlation formula with a value of 0.752 which means getting the strength of the relationship between Variable X and Variable Y.